Single and mixed effects of seven heavy metals on stroke risk: 11,803 adults from National Health and Nutrition Examination Survey (NHANES) - Huang, Xinyi; Wu, Yueran; Lu, Yan (Frontiers in Nutrition, 2025)
BackgroundThe accumulation of heavy metals in soil and plants poses risks to food safety. Human exposure to heavy metals has been linked to stroke risk, though research on this connection is limited and findings are inconsistent.MethodsWe estimated the associations of 7 blood metals [cadmium (Cd), lead (Pb), mercury (Hg), manganese (Mn), copper (Cu), selenium (Se), and zinc (Zn)] with the risk of stroke among 11,803 U.S. adults. Logistic regression account for the intricate sampling design and restricted cubic spline (RCS) was used to explore the associations between single heavy metal and stroke risk. The weighted quantile sum (WQS) and quantile g-computation (qgcomp) were employed to explore the joint effects of seven metals on stroke. Potential confounders were adjusted.ResultsAfter adjusting for the potential confounders, the logistic regression analysis showed the log-transformed Cd and Zn level was associated with stroke (All p < 0.05). After adjusting for the potential confounders, the logistic regression analysis showed the log-transformed Cd and Zn level was associated with stroke (All p < 0.05). WQS and qgcomp analyses consistently demonstrated a positive correlation between metals-mixed exposure and stroke risk, identifying Cd and Cu as key contributors to the outcomes, while Zn may serve as a protective factor.ConclusionThese findings indicated that heavy metal exposure is associated with stroke risk, and the protective effect of Zn on stroke risk deserves further research to verify.